IDENTITAS CRYPTOCURRENCY : HALAL DAN HARAM - Rahmah, Syahidah; Jannah, Miftahul (Jurnal Ar-Ribh, 2021)
Cryptocurrency is a form of digital storage that uses cryptographic techniques or secret passwords. This cryptocurrency is not controlled by an institution such as a bank, country or certain company but uses a decentralized server and cryptocurrency uses a system that cannot be controlled by anyone because it uses a network that can document transactions directly, without any third party. This review expects to get a thought meaning of Cryptocurrency and how the assessment of the researchers on it depends on sharia and Islamic law. This examination is a writing study. The information wellsprings of this examination were taken from the Qur'an, the hadith of the Prophet, traditional and contemporary books, the assessments of researchers just as from online media sources. From this exploration, it was discovered that Cryptocurrency or the utilization of virtual money can without a doubt be perceived as a brilliant progressive innovation, but its use as an investment instrument contains elements of maysir (betting) and as a business transaction instrument that contains elements of gharar, it contains tyranny and that including transactions that are prohibited in Islam.Keywords : Enterpreneurship, Cryptocurrency and Islamic Law.